Pengaruh Pelatihan dan Pengalaman Kerja Terhadap Pengembangan Sumber Daya Manusia Aparatur Dinas Kebudayaan, Pariwisata dan Ekonomi Kreatif Kabupaten Simalungun - Dermawan Perangin-angin; Dasmaika Apriani Haloho; Nursahrina Sinaga; Yulita SN Girsang (CV. ULIL ALBAB CORP, 2024)
Development of human resources is very important for agencies or organizations because they have a role as a driving force for all activities in managing, organizing and carrying out the activities of agencies or organizations. Quality human resources will produce good performance results in accordance with their work targets. The purpose of this study was to analyze the effect of training and work experience on the development of human resources for the apparatus of the Simalungun District Health Office. The population of this study was the Simalungun District Health Office apparatus, consisting of 60 people. The entire population is used as a sample. This study uses Multiple Linear Regression analysis and hypothesis testing with the F-test and t-test. The results of this study indicate that training has an effect on human resource development, work experience has an effect on human resource development. Training and Work Experience simultaneously influence the Development of Human Resources for the Simalungun District Health Office Apparatus. It is hoped that agencies will pay more attention to trainer instructors in training, apparatus work experience related to the duties of the apparatus to be carried out, development of human resources for lead apparatus to provide apparatus to participate in training, education, workshops and supported by apparatus work experience.